Integrins mediate symbiont-specific uptake in cnidarian larvae - Jones, Victor; Dörr, Melanie; Siemers, Isabelle; Rupp, Sebastian; El Hilali, Sami; Brites, Sara; Surm, Joachim M.; Mägele, Ira; Gornik, Sebastian G.; Ferguson, Meghan; Guse, Annika (EMBO reports, 2026)
Endosymbiosis between dinoflagellate algae and cnidaria is fundamental for coral reef health. Appropriate symbiont selection is required for sufficient host nutrient acquisition and could be tailored to increase cnidarian stress tolerance. Previous research suggested glycan-lectin interactions facilitate symbiont uptake; however, blockage of such interactions does not fully inhibit symbiosis establishment, suggesting other receptors are at play. Here, we use a combination of cnidarian model systems and human cell lines to determine if phagocytic integrins facilitate symbiont recognition and uptake. Integrins are highly expressed in the gastrodermal tissue of the host, where symbiosis takes place, and symbiont uptake alters the expression of integrins and downstream signaling molecules. Blockage of integrin binding sites with competitor peptides reduces symbiont uptake, while uptake of non-symbiotic algae, or uptake in a non-symbiotic cnidarian, is unaffected. Finally, overexpression of phagocytic integrins in human cells increases symbiont uptake, and mutation of the active binding site abolishes uptake. Our findings reveal integrins as important receptors for symbiosis establishment and shed light on the evolutionary functions of integrins during phagocytosis.
Online veröffentlicht: 16. Dezember 2025
Gesehen am 11.02.2026